A parsimonious neutral model suggests Neanderthal replacement was determined by migration and random species drift - Oren Kolodny (Nature Portfolio, 2017)
The replacement of Neanderthals by modern humans is thought to have been due to environmental factors, a selective advantage of modern humans, or both. Here, Kolodny and Feldman develop a neutral model of species drift showing that rapid Neanderthal replacement can be explained parsimoniously by simple migration dynamics.